Insight into the Interaction Mechanism of Pseudorabies Virus Infection - Xiaoyong Chen; Ziding Yu (Biology)
The pseudorabies virus (PRV), also known as suid alphaherpesvirus 1 (SuAHV-1), has garnered significant attention due to its broad host range and the economic losses it incurs in the swine industry. This review aims to provide a comprehensive understanding of the intricate virus–host interactions during PRV infection, focusing on the evasion strategies of the virus against the host responses. We also summarize the mechanisms by which PRV manipulates the host cell machinery to facilitate its replication and spread, while simultaneously evading detection and clearance by the immune system. Furthermore, we discuss the latest advancements, such as metabolic, autophagic, and apoptotic pathways in studying these interactions, highlighting the role of various cellular factors and pathways in elucidating virus–host dynamics. By integrating these insights, the article aims to provide a comprehensive overview of the molecular mechanisms underlying PRV pathogenesis and host response, paving the way for the development of novel therapeutic strategies against this virus.